Urgensi Pelaksanaan Sistem Cashless Government dalam Membangun Birokrasi yang Transparan dan Akuntabel - Kurniati, Paramita Nur; Nugroho, Bernardus Yuliarto (Universitas Medan Area, 2019)
Public demands for transparent and accountable bureaucracy and increasingly dynamic environmental conditions have prompted the Government to implement cashless government system in order to modernize the transaction of the State Budget (Anggaran Pendapatan dan Belanja Negara - APBN). The cashless governmenst system is considered as part of public innovation in order to encourage public sector administrative reform efforts. Apart from the pros and cons that arise, the government's cashless policy in government expenditure is expected to take strategic steps in the budget that are in line with the principles of flexibility, security, effectiveness and accountability. The purpose of this study is to (1) explain current government transaction conditions, (2) understand the concept of cashless government, and (3) elaborate on the urgency of implementing the cashless government system in Indonesia. The literature study in this paper shows that there are still weaknesses and potential corruption caused by the number of transactions carried out by the government. It is important to create an urgent need or foster a sense of urgency for change in public sector organizations and by immediately transforming into a dynamic bureaucracy in the face of the challenges of the times. The government's cash system is expected to increase the transparency and accountability of the State's finances and approve the payment of acts of corruption. In a broader context, this system is expected to provide benefits in encouraging economic growth and improving public welfare.